1996
DOI: 10.1007/bf01670106
|View full text |Cite
|
Sign up to set email alerts
|

Preschoolers' responses to ongoing interadult conflict: The role of prior exposure to resolved versus unresolved arguments

Abstract: Children's past experiences with interadult conflict are likely to influence their responses to ongoing arguments. Preschoolers' (4- to 5-year-olds) responses to interadult conflict were examined as a function of experimentally manipulated histories of exposure to resolved and unresolved arguments. Children were presented with two live arguments that were either resolved or unresolved, then they were presented with a third argument that was interrupted in progress (i.e., unresolved), and they were interviewed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 43 publications
2
35
0
Order By: Relevance
“…Over time, exposure to unresolved conflict affects the way children perceive many conflicts. Children randomly assigned to see an unresolved conflict reacted to a later ambiguous conflict with more behavioural distress, negative perceptions of the conflicting couple, and greater representations of the couple's relationship as unstable than children assigned to see a resolved conflict (El-Sheikh & Cummings, 1995;El-Sheikh, Cummings, & Reiter, 1996). Thus, when parents are unable to work toward the resolution of conflict, such as when parents stonewall, children may perceive conflict as particularly threatening and be highly motivated to intervene in disputes.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Over time, exposure to unresolved conflict affects the way children perceive many conflicts. Children randomly assigned to see an unresolved conflict reacted to a later ambiguous conflict with more behavioural distress, negative perceptions of the conflicting couple, and greater representations of the couple's relationship as unstable than children assigned to see a resolved conflict (El-Sheikh & Cummings, 1995;El-Sheikh, Cummings, & Reiter, 1996). Thus, when parents are unable to work toward the resolution of conflict, such as when parents stonewall, children may perceive conflict as particularly threatening and be highly motivated to intervene in disputes.…”
Section: Discussionmentioning
confidence: 84%
“…Most notably, the current study employs a cross-sectional design and definitive statements about causality cannot be made. Both theory and previous longitudinal research have established that parental alcohol problems and marital conflict precede children's emotional insecurity and adjustment difficulties , and experimental studies have found that exposure to marital conflict is causally related to children's reactions to conflict (El Sheikh & Cummings, 1995;El Sheikh et al, 1996). However, current research also suggests that children's behavioural problems predict later marital conflict and parental stress (Jenkins, Simpson, Dunn, Rasbash, & O'Connor, 2005).…”
Section: Discussionmentioning
confidence: 87%
“…Among the most distressing conflicts are those that involve physical aggression (Cummings, Vogel, Cummings, & El-Sheikh, 1989;Cummings, Zahn-Waxler, & Radke-Yarrow, 1981). Conflicts that are well resolved lead to less negative impact on children (Cummings, Ballard, El-Sheikh, & Lake, 1991;Cummings, Simpson, & Wilson, 1993;El-Sheikh, Cummings, & Reiter, 1996), as well as more positive predictions about the future (El-Sheikh & Cummings, 1995), contributing to emotional security. However, marital conflicts that result in physical violence are by definition not well resolved.…”
Section: * * *mentioning
confidence: 96%
“…This behavioral impulse was chosen because of its high frequency, and because it is the most frequently reported response in this context (e.g., El-Sheikh & Cummings, 1992). Gender was included in analyses because it has often been related to reports of wanting to stop interadult arguments (e.g., El-Sheikh, Cummings, & Reiter, 1995).…”
Section: Verbal Responsesmentioning
confidence: 99%